2020
DOI: 10.1017/wet.2020.30
|View full text |Cite
|
Sign up to set email alerts
|

Improved herbicide selectivity in tomato by safening action of benoxacor and fenclorim

Abstract: Safeners have been widely used to reduce phytotoxicity to crops, thus serving as an alternative weed control strategy. Benoxacor and fenclorim safeners have the potential to protect plants from herbicide phytotoxicity by increasing glutathione S-transferase (GST) activity within the plant. The study aimed to evaluate the safening effect of benoxacor and fenclorim on tomato against selected herbicides applied POST. The experiment was conducted in a greenhouse in a completely randomized designed with four replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The mixture of fluazifop-p-butyl with fomesafen with and without adjuvant caused a moderate intoxication to crop plants (Figures 1A and 2A) and the number of fruits did not differ from the control with weeding (Table 3). The intoxication observed in plants from experiments I and II was probably due to fomesafen, because, when applied alone, Castro et al (2020) observed reductions of up to 62% in tomato plants, compared to the control without herbicides. When there is a mixture of fluazifop-p-butyl + fomesafen, the formulation acquires a broad spectrum of weed control (Silva & Silva, 2007), which may be a viable alternative for the cultivation of P. angulata, insofar as future works indicate the possibility of a later application compared to those used in this experiment, since the results in field proved to be promising (Table 3).…”
Section: Field Experiments (Eiii)mentioning
confidence: 86%
“…The mixture of fluazifop-p-butyl with fomesafen with and without adjuvant caused a moderate intoxication to crop plants (Figures 1A and 2A) and the number of fruits did not differ from the control with weeding (Table 3). The intoxication observed in plants from experiments I and II was probably due to fomesafen, because, when applied alone, Castro et al (2020) observed reductions of up to 62% in tomato plants, compared to the control without herbicides. When there is a mixture of fluazifop-p-butyl + fomesafen, the formulation acquires a broad spectrum of weed control (Silva & Silva, 2007), which may be a viable alternative for the cultivation of P. angulata, insofar as future works indicate the possibility of a later application compared to those used in this experiment, since the results in field proved to be promising (Table 3).…”
Section: Field Experiments (Eiii)mentioning
confidence: 86%
“…β‐CC itself has a low toxicity causing little damage to leaves (Figure 8C). Thus, the action of β‐CC resembles the function of herbicide safeners, that is, chemicals of low toxicity able to induce enzymes involved in the detoxification and metabolization of herbicides (Castro et al, 2020; Riechers et al, 2010). Herbicide safeners offer important agricultural perspectives in alternative weed control strategies to increase herbicide selectivity in crops.…”
Section: Discussionmentioning
confidence: 99%
“…GSH, an essential substance in the metabolic detoxification process, conjugates with xenobiotics, such as pesticides or heavy metals, spontaneously or catalyzed by GSTs to inactivate them. 46 This process is presumed to be requisite for the metabolite's transport into the vacuole (phase III) and possible further breakdown within the vacuole (phase IV). GSTcatalyzed GSH conjugation is essential for removing toxic substances from the cytosol and preventing their interaction with targets.…”
Section: ■ Effects Of Safeners On Herbicide Metabolism In Plantsmentioning
confidence: 99%